2016
DOI: 10.1097/bor.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Behçet's disease

Abstract: Genetic and epigenetic changes affecting cells and molecules involved in Behçet's disease offer new pathways for research, including cytoskeletal protein function, that will provide new targets for therapy, and potentially address the ethnic differences seen in validation of gene studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…microRNA-155 (miR-155) is one of the most important miRNAs and plays an important role in various biological processes, including immunity [2,3],inflammation [4,5], viral infections [6], cancer [7,8] and cardiovascular disease [9,10]. The homeostasis of inflammation and inflammatory cells is closely related to miR-155 expression and plays a critical role in T cell and B cell development [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…microRNA-155 (miR-155) is one of the most important miRNAs and plays an important role in various biological processes, including immunity [2,3],inflammation [4,5], viral infections [6], cancer [7,8] and cardiovascular disease [9,10]. The homeostasis of inflammation and inflammatory cells is closely related to miR-155 expression and plays a critical role in T cell and B cell development [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Its aetiology is unknown but likely involves interplay between genetic and environmental factors [1]. BD has a very heterogeneous and unpredictable phenotype with the potential to involve the cardiovascular, renal, gastrointestinal, pulmonary, vascular, musculoskeletal, urological and central nervous systems to varying degrees [24].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies demonstrated that inflammatory mediators are highly expressed in patients with BD compared to healthy controls [12] , mainly represented by Th1 and Th17 cells cytokines. In the same way, genetic polymorphisms of inflammatory mediators are associated with disease susceptibility and evolution [13] .…”
Section: Introductionmentioning
confidence: 99%